Do Job-to-Job Transitions Drive Wage Fluctuations Over the Business Cycle? - Karahan, Fatih; Michaels, Ryan; Pugsley, Benjamin; Şahin, Ayşegül; Schuh, Rachel (American Economic Review, 2017)
We investigate the importance of job-to-job (JJ) transitions for cyclical wage dynamics. By exploiting cross-state variation, we find that wage growth is tightly linked to variation in the JJ transition probability, and conditional on this, the job finding probability of the unemployed has no explanatory power. We investigate the robustness of our results to several caveats and find the result to hold. Finally, we discuss the implications of our findings for competing theories of wage dynamics.